2021
DOI: 10.1038/s41401-021-00637-0
|View full text |Cite
|
Sign up to set email alerts
|

Triptolide protects against white matter injury induced by chronic cerebral hypoperfusion in mice

Abstract: White matter injury is the major pathological alteration of subcortical ischemic vascular dementia (SIVD) caused by chronic cerebral hypoperfusion. It is characterized by progressive demyelination, apoptosis of oligodendrocytes and microglial activation, which leads to impairment of cognitive function. Triptolide exhibits a variety of pharmacological activities including anti-inflammation, immunosuppression and antitumor, etc. In this study, we investigated the effects of triptolide on white matter injury and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…The same process without carotid ligation was operated on the sham group. Body temperature was sustained until mice were woken from anesthesia [39][40][41][42][43].…”
Section: Animalsmentioning
confidence: 99%
“…The same process without carotid ligation was operated on the sham group. Body temperature was sustained until mice were woken from anesthesia [39][40][41][42][43].…”
Section: Animalsmentioning
confidence: 99%
“…In addition, right unilateral common carotid artery occlusion (rUCCAO), which simulates chronic cerebral hypoperfusion, can also be used for cerebral ischemia related research ( Yoshizaki et al, 2008 ). A recent study using rUCCAO and OGD reported the therapeutic effects of triptolide in vitro and in vivo , including alleviating white matter injury, protecting against oligodendrocyte apoptosis directly, and inhibiting microglial inflammation indirectly, and the related mechanism was to increase the phosphorylation of the Src/AKT/GSK 3β singnaling pathway ( Wan et al, 2022 ).…”
Section: Effects Of Triptolide and Celastrol On Brain And Spinal Cord...mentioning
confidence: 99%
“…Moreover, the WMI model lacks an in vitro model; therefore, we used an OGD model to mimic demyelination in vivo. Although the OGD model has been widely used to investigate the proliferation and differentiation of oligodendrocytes (Dai et al., 2020; Wan et al., 2022; Wu et al., 2014), it is not a perfect fit for the chronic hypoxia‐induced WMI model and cannot fully capture the complex pathogenesis observed in vivo. A more appropriate in vitro model is looked forward to.…”
Section: Discussionmentioning
confidence: 99%